Boosting Electrocatalytic Oxygen Evolution over Ce−Co9S8 Core–Shell Nanoneedle Arrays by Electronic and Architectural Dual Engineering. Issue 32 (26th April 2022) - Liu, Kun; Zhu, Zhuoya; Jiang, Mengqi; Li, Liangcheng; Ding, Linfei; Li, Meng; Sun, Dongmei; Yang, Gaixiu; Fu, Gengtao; Tang, Yawen
Abstract: An dual electronic and architectural engineering strategy is a good way to rationally design earth‐abundant and highly efficient electrocatalysts of the oxygen evolution reaction (OER) for sustainable hydrogen‐based energy devices. Here, a Ce‐doped Co9 S8 core–shell nanoneedle array (Ce−Co9 S8 @CC) supported on a carbon cloth has been designed and developed to accelerate the sluggish kinetics of the OER. Profiting from valance alternative Ce doping, a fine core–shell structure and vertically aligned nanoneedle arrayed architecture, Ce−Co9 S8 @CC integrates modulated electronic structure, highly exposed active sites, and multidimensional mass diffusion channels; together, these afford a favorable catalyzed OER. Ce−Co9 S8 @CC exhibits remarkable performance in the OER in an alkaline medium, where the overpotential requires only 242 mV to deliver a current density of 10 mA cm −2 for the OER; this is 70 mV superior to that of Ce‐free Co9 S8 catalyst and other counterparts. Good stability and impressive selectivity (nearly 100 % Faradic efficiency) are also demonstrated. When integrated into a two‐electrode OER//HER electrolyzer, the as‐prepared Ce−Co9 S8 @CC displays a low operation potential of 1.54 V at 10 mA cm −2 and long‐term stability, thus demonstrating great potential for economical water electrolysis. Abstract : Rare‐earth‐based nanomaterials for catalysis : Ce‐doped Co9 S8 core–shell nanoneedle arrays, vertically aligned on carbon cloth (Ce−Co9 S8 @CC) were prepared in situ by calcining a Ce−Co(CO3 )0.5 OH@CC precursor. The Ce‐incorporated Co9 S8 active component and core–shell nanoneedle arrayed architecture give Ce−Co9 S8 @CC a refigured electronic configuration, highly exposed active sites and multidimensional mass diffusion channels. Benefitting from these dual electronic and architectural advantages, Ce−Co9 S8 @CC exhibits superior electrocatalytic activity, stability and selectivity toward the oxygen evolution reaction.